Integrasi spasial dalam perancangan batas fisik perumahan kota, Studi kasus: Perumahan Setra Duta, Bandung, Jawa Barat - Fauziyyah Sofiyah Radliyatullah; Yohanes Basuki Dwisusanto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Spatial integration in physical boundary design of urban housing The increasing number of residents of a city, the higher level of citizens' need for housing. The community's need for housing is answered by the developer by building housing in several areas. However, the phenomenon that occurs at this time is that the housing development often does not pay attention to the existence of existing settlements first, so that physical boundaries are created with poor physical spatial quality and create barriers between new housing and the surrounding environment. The physical boundaries that frame the city's housing complex certainly lead to the phenomenon of spatial segregation in the surrounding environment. Hence, the main purpose of this journal is to find out the extent of spatial integration that is applied to the physical boundaries of Setra Duta Bandung housing. The discussion method is carried out by analyzing problems and opportunities that arise at the physical boundaries in the study area, synergizing with the study of literature on spatial integration in the physical boundaries of urban housing. During the observations, it was found that the physical boundaries of Setra Duta housing showed spatial segregation with the part of the city that surrounds it. Spatial segregation is created as a result of something physical that causes or clarifies differences. This phenomenon brings negative impacts such as deteriorating the physical quality of spatial and shared space in the housing border area. © 2020 Fauziyyah Sofiyah Radliyatullah, Yohanes Basuki Dwisusanto